Nonreciprocal charge transport up to room temperature in bulk Rashba semiconductor α-GeTe - Yan Li (Nature Portfolio, 2021)
Most work on nonreciprocal transport is limited to cryogenic temperatures due to the low Rashba spin splitting energy. Here, the authors report a nonreciprocal charge transport behavior up to room temperature in semiconductor α-GeTe with coexisting the surface and bulk Rashba states.